Management and biosecurity practices associated with Mycoplasma bovis seropositivity in Swedish dairy herds: a questionnaire study - Alvåsen, Karin; Hurri, Emma; Magnusson, Hanna; Tråvén, Madeleine (Frontiers in Veterinary Science, 2025)
Background and objectiveMycoplasma (M.) bovis is a significant cause of pneumonia and mastitis in cattle worldwide and is recognized for its impact on both animal welfare and farm economics. In the absence of an effective vaccine or treatment, control and prevention efforts rely on identifying risk factors associated with both within- and between-herd transmission. The aim of this study was to investigate associations between herd-level M. bovis seropositivity and biosecurity and management routines in Swedish dairy herds.MethodologyAn online questionnaire was distributed to 146 dairy farmers in southern Sweden. The questionnaire contained 66 closed questions regarding external and internal biosecurity, calf management practices, milking routines and animal health. The targeted herds were already participating in another study, in which bulk tank milk and milk from primiparous (PP) cows were collected and analysed with IDvet ELISA to detect M. bovis antibodies.ResultsThe response rate to the questionnaire was 79% (n = 115) and herds were categorized as antibody negative if both bulk tank milk and samples from PP cows were negative. Of the participating herds, 31% (n = 36) were categorized as antibody positive as they had positive bulk tank milk and/or positive PP cows. Many farm management practices, such as purchase of cattle, were similar between M. bovis antibody-negative and antibody-positive herds. As a result, few management factors showed a significant association with M. bovis status. For external biosecurity, affiliation to the national biosecurity program (“Smittsäkrad besättning”) was associated with M. bovis antibody-negative status. Regarding internal biosecurity, feeding calves with milk replacer and housing weaned calves in groups of more than 15 were more common in M. bovis antibody-positive herds. Mycoplasma bovis status was also associated with animal health, as antibody-positive herds reported higher numbers of youngstock over 6 months of age that required treatment or euthanasia due to arthritis.ConclusionThese findings indicate that both internal and external biosecurity measures, including participation in a national biosecurity program and specific calf management practices, may contribute to reducing the risk of M. bovis infection in dairy herds.